ANALISA KEPUTUSAN PENDAMPINGAN ANAK USIA 28 HARI – 6 TAHUN YANG DIRAWAT DI RUMAH SAKIT - Nugrah Dwi Novendi; Emi Nurlaela; Herni Rejeki (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The decision to mentor a young children is the result of constant thought of escorting the children by the father and or the mother or as a form of assuming their responsibility. The goal of this study is to determine the relationship among being employed, anxiety, able to care, and psychological closeness of the family leader to word the decision to mentor children aged 28 days - 6 years who are treated at the Islamic Hospital of PKU Muhammadiiyah Pekajangan of Pekalongan district. This research uses descriptive analytical design by applying Cross Sectional approach. The Sampling technique uses accidental sampling. The number of respondents are as many as 36 people. The  results of bivariate statistical tests uses the chi square with α < 5% to determine the relationship among being employed, anxiety, able to care, and psychological closeness of the family leader to word the decision to mentor children aged 28 days - 6 years who are treated at the Islamic Hospital of PKU Muhammadiiyah Pekajangan of Pekalongan district. The result shows that there is a relationship between employment with the decision to mentor children with ρ value 0.040, there is a relationship between the anxiety of family leader with the decision to mentor of corresponding children with ρ value 0.048, there is a relationship between the able to care with the decision to mentor children with ρ value 0.048 and there is no relationship between psychological closeness of the family leader and the children with the decision to mentor children with ρ value 1.000. Therefore, the hospital is expected to provide facility for children escorting and to improve child care programs.Keywords : children aged 28 days-6 years, decision to mentor, hospitalization.